A novel technique for in-situ simultaneous measurement of thickness of deposited film and electron density with two curling probes. (22nd July 2020) - Ogawa, Daisuke; Nakamura, Keiji; Sugai, Hideo
Abstract: We have developed a technique for measuring the thickness of a deposited film and electron density simultaneously during plasma processing with two different-sized curling probes. The technique requires only two things; the measurement of resonant-frequency shifts occurring on the two probes before and after the processing, and the substitution of the frequencies into a set of two quadratic equations. The solutions of the equations lead to a simulated measurement of electron density and the thickness of films deposited on the probe surface. We placed a piece of polyimide tape on the probe surface to simulate the deposited film, and then exposed the probes to an argon plasma. In this report, we derived the thickness and pre-calibrated electron density simultaneously from the frequency shifts due to the film thickness and the plasma density. Our measurement showed the film thickness with 9% accuracy and the electron density in the order of 10 9 cm −3 . This result revealed that the proposed technique is principally available for plasma processing.